Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Penghargaan terhadap Kinerja Karyawan: (Studi pada Karyawan Lulu Hypermarket Departement Store Cabang BSD Tangerang) - Yohana Tindaon; Hari Subagio (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the Influence of Leadership Style, Work Environment, and Rewards on Employee Performance at Lulu Hypermarket Department Store BSD Tangerang Branch. The method used is multiple linear regression analysis method using SPSS software version 22. And the technique used is Non Probability Sampling with saturated sampling type. The results of this study indicate the regression value is Y = 34.997 + 0.401 X1 -0.409 X2 +0.082 X3 + ε That Leadership Style (X1) has a significant effect on Employee Performance, This shows the importance of the role of a leader/manager in improving employee performance to achieve organizational goals. Work Environment (X2) has a negative and significant effect on Employee Performance, This shows that an unsupportive Work Environment can reduce Employee Performance. While Rewards (X3) have no effect and are not significant on Employee Performance (Y), Recognition or giving gifts is still very important to improve Employee Performance. The contribution of the three independent variables R2 is 33.3% to Employee Performance (Y) and the remaining 66.7% is influenced by other factors.